2017
DOI: 10.1002/adv.21869
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and optimization of electrospinning of polyvinyl alcohol (PVA)

Abstract: The electrospun fibers can have applications in diverse fields, such as tissue scaffolds, optical electronics, nanocatalysis, and sound absorption. Nanoscale fibers with a higher surface area can provide superior mechanical, physical, and thermal properties. Therefore, investigation of the factors affecting the electrospinning process, for various materials, is required. In this study, the design of experiments issued for optimization of electrospinning of polyvinyl alcohol (PVA). Analysis of variance (ANOVA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…In initial experiments, the conductivity and viscosity of polymer solutions for electrospinning containing PVA in water–ethanol solution (9:1) and various amounts of the thiosemicarbazone HapyTSCmB ( N 4-( S )-1-phenylethyl)-2-(pyridin-2-yl-ethylidene)hydrazine-1-carbothioamide, Scheme 1 ) were measured ( Figure 1 ). The conductivity and viscosity of electrospinning polymer solutions have a strong impact on the morphology and diameter of PVA fibers [ 36 , 37 , 61 , 62 , 63 , 64 ]. We found that adding 10 wt% of the TSC to the PVA solution caused a slight increase (approximately 6.5%) in conductivity and a significant decrease of about 83% in the viscosity ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In initial experiments, the conductivity and viscosity of polymer solutions for electrospinning containing PVA in water–ethanol solution (9:1) and various amounts of the thiosemicarbazone HapyTSCmB ( N 4-( S )-1-phenylethyl)-2-(pyridin-2-yl-ethylidene)hydrazine-1-carbothioamide, Scheme 1 ) were measured ( Figure 1 ). The conductivity and viscosity of electrospinning polymer solutions have a strong impact on the morphology and diameter of PVA fibers [ 36 , 37 , 61 , 62 , 63 , 64 ]. We found that adding 10 wt% of the TSC to the PVA solution caused a slight increase (approximately 6.5%) in conductivity and a significant decrease of about 83% in the viscosity ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Taguchi's method, being simple and robust, was used in this study for the design of experiments and the optimization. The design consists of 27 rows and 13 columns (max) with three-level variation [38]. The mean output performance and variation were studied with the applied Taguchi's quality loss function design.…”
Section: Design Of Experimentsmentioning
confidence: 99%
“…Furthermore, in order to determine “accuracy”, i.e., confidence level of the Taguchi S/N approach, results of the confirmation experiment could be compared with the estimated values. For this purpose, the “estimated S/N ratio” can be calculated by using the following relation 28 : SNestimated=SNM+i=1n()SNiSNM where SNM is the total mean of the S/N ratio while SNi is the mean of the S/N ratios for each parameter level. Then, the “estimated average diameter” can be calculated by using the relation: SNestimated=10log()destimated2 …”
Section: Resultsmentioning
confidence: 99%
“…In the literature, although the Taguchi technique has been used to optimize electrospinning parameters of various polymer nanofibers 21–31 ; the number of the studies reported so far for the PLA‐based materials are extremely limited. There are only two studies reported for the neat PLA and one study reported for the halloysite nanotube (HNT) filled PLA, as summarized below.…”
Section: Introductionmentioning
confidence: 99%